"We Live in a Technological Era, Whether You Like It or Not": Client Perspectives and Online Welfare Applications. (July 2014) - Hetling, Andrea; Watson, Stevie; Horgan, Meghan
A growing number of state welfare agencies are using the Internet to communicate with potential and current clients. Although public management benefits are clear, little is known about client perspectives. This mixed-methods research project examines the topics of application security, reliability, appropriateness, and ease of use, and personal experiences of potential users to understand opinions of online welfare applications. Focus group findings highlight direct benefits, such as speed and ease of use, and indirect benefits, such as holding caseworkers accountable and avoiding unpleasant office conditions. Study participants also identified exceptions like emergencies and applicants with special needs. Despite mixed feelings, many participants preferred online applications to in-person, worker-led eligibility interviews.